Linking Hydraulic Properties to Hemolytic Performance of Rotodynamic Blood Pumps. Issue 9 (11th July 2022) - Escher, Andreas; Hubmann, Emanuel Johannes; Karner, Barbara; Messner, Barbara; Laufer, Günther; Kertzscher, Ulrich; Zimpfer, Daniel; Granegger, Marcus
Abstract: In rotodynamic blood pumps (RBPs) a substantial proportion of input energy is dissipated into the blood. This energy may propel damaging work on blood constituents. To date, the link between this hydraulic energy dissipation and respective hemolytic action in RBPs remains vastly unknown. In this study, computational fluid dynamics is applied to compute the hydraulic energy dissipation at 9 operating conditions in two RBPs (HM3: HeartMate 3; HVAD: HeartWare Ventricular Assist Device). Respective interrelations with hemolytic pump performance are elucidated by comparing these computations with in silico predicted and in vitro measured hemolysis. Despite different pump geometries, hydraulic loss magnitudes, and distributions, global hydraulic energy dissipation shows strong correlation ( r > 0.95) to in vitro hemolysis with scaling factors in the same order of magnitude for both devices ( φ HM3 = 0.599 (mL g) (J 100L) –1 ; φ HVAD = 0.716 (mL g) (J 100L) –1 ). The analytical description of hydraulic energy dissipation reveals to be a function of shear stresses and exposure time, unmasking its analogy to the power‐law formulation of hemolysis. This hydraulics‐based analysis may denote a step ahead to relate turbomachinery to bioengineering and may provide mechanistic insights into the relation between RBP design, hydraulic properties, and hemolytic performance. Abstract : During the operation of rotodynamic blood pumps, a considerable extent of input energy is dissipated into the blood. In a combination of computational fluid dynamics and experimental hemolysis examination this hydraulic energy dissipation reveals to correlate well with respective in vitro hemolysis in two prominent pumps, while unmasking an analogy to the power‐law formulation of hemolysis.